Assessing fidelity of cognitive behavioral therapy in rural VA clinics: design of a randomized implementation effectiveness (hybrid type III) trial. (December 2015) - Cucciare, Michael; Curran, Geoffrey; Craske, Michelle; Abraham, Traci; McCarthur, Michael; Marchant-Miros, Kathy; Lindsay, Jan; Kauth, Michael; Landes, Sara; Sullivan, Greer
Abstract Background Broadly disseminating and implementing evidence-based psychotherapies with high fidelity, particularly cognitive behavioral therapy (CBT), has proved challenging for many health-care systems, including the Department of Veterans Affairs, especially in primary care settings such as small or remote clinics. A computer-based tool (based on the coordinated anxiety learning and management (CALM) program) was designed to support primary care-based mental health providers in delivering CBT. The objectives of this study are to modify the CALM tool to meet the needs of mental health clinicians in veterans affairs (VA) community-based outpatient clinics (CBOCs) and rural "veterans", use external facilitation to implement CBT and determine the effect of the CALM tool versus a manualized version of CALM to improve fidelity to the CBT treatment model, and conduct a needs assessment to understand how best to support future implementation of the CALM tool in routine care. Methods/design Focus groups will inform the redesign of the CALM tool. Mental health providers at regional VA CBOCs; CBT experts; VA experts in implementation of evidence-based mental health practices; and veterans with generalized anxiety disorder, panic disorder, social anxiety disorder, posttraumatic stress disorder, "with or without" depression will be recruited. A hybrid type III design will be used to examine the effect of receiving CBT training plus either the CALM tool or a manual version of CALM on treatment fidelity. External facilitation will be used as the overarching strategy to implement both CBT delivery methods. Data will also be collected on symptoms of the targeted disorders. To help prepare for the future implementation of the CALM tool in VA CBOCs, we will perform an implementation need assessment with mental health providers participating in the clinical trial and their CBOC directors. Discussion This project will help inform strategies for delivering CBT with high fidelity in VA CBOCs to veterans with anxiety disorders and PTSD with or without depression. If successful, results of this study could be used to inform a national rollout of the CALM tool in VA CBOCs including providing recommendations for optimizing the adoption and sustained use of the computerized CALM tool among mental health providers in this setting. Trial registration ClinicalTrials.gov, NCT02488551